(untitled) (American Journal of Islam and Society, 1991)
Contrasting Epistemics “why if a fish came to me and told me he was going on a journey, I should say, With what porpoise?”’ “Don’t you mean burpose’?” said Alice. “I mean what I say,” the Mock Turtle replied in an ofended tone. (Lewis Carroll, Alice in Wonderland) Consider this analogy: There was a man beneath a tree. He wished to collect his thoughts, but the sparrows disturbed him with their chirping. He would chase them with his stick and then resume his train of thought, but the sparrows would come back and he would have to scare them away. . . Eventually someone told him: %is is like being a slave at the wheel going round and round forever. Ifyou want to escape the vicious circle, you shouldfell the tree: Imam al Ghazali, (Ihya’ ‘Ulum al Din) Cultural Parodies: Shaping a Discourse Abstract It has been the practice for the dominant paradigm to set the terms of rational discourse and for the “Other” to defer in reverence - if it wanted to be admitted to the circle of respectability. In this case, the tables are turned MOM Abul-Fadl directs the Research Project on Western Thought at the International Institute of Islamic Thought, Herndon, Virginia and is the chairperson of the Political Science Discipline Council of the Association of Muslim Social Scientists. and the dominant paradigm, which is secularist, is viewed critically through the lens of a re-emerging tawhidi paradigm. The purpose is not to engage in a test of will or vision, but to lay the ground for a discourse which can accommodate a genuine diversity-in-dignity for all, and which would include Self and Other in a re-formed world of inter-relatedness developed through new categories and points of reference. In a common human heritage rich in communicable symbols and transitive experiences, cultivating the terms of a hermeneutic of mutuality is imminent. Its objectives would be to redefine and assure worldly morality and rationality at higher levels of reality. Only then can the self-imposed constraints, constrictions, and anomalies which are inherent in the prevailing culture be transcended. The context for shaping this discourse can be as broad and encompassing or as concrete and particular as the response in the concurrent fields of the humanities and the social sciences will admit ...